Strategies of Hearing Preservation With Military Personnel: A Scoping Review - Heupa, Adriana Betes; Simões, Pierângela Nota [UNESP]; de Araújo, Cristiano Miranda; Meira Taveira, Karinna Veríssimo; Renata José, Maria [UNESP]; de Oliveira Gonçalves, Claudia Giglio; Lüders, Débora (American Speech Language Hearing Association, 2024)
Purpose: The purpose of this study was to map the strategies used in hearing health education with military personnel during the Hearing Preservation Program (HPP). Method: This study is a scoping review, with electronic searches conducted in online databases and gray literature: Latin American and Caribbean Literature in Health Sciences, PubMed/Medline, Scopus, Web of Science, ASHAWire, Google Scholar, and ProQuest Dissertation & Theses. Only studies describing, analyzing, or evaluating the application of the HPP to active duty or training military personnel were included. Results: A total of 3,478 references were retrieved, and 12 studies met the inclusion criteria. The strategies were classified into five categories: focus group aimed at exploring knowledge and perceptions regarding hearing health (five studies), training on the proper fitting of hearing protection devices (four studies), the utilization of audiovisual materials (seven studies), questionnaires administrated before and after educational intervention (five studies), and feedback survey concerning the implemented hearing health education (three studies). Conclusion: There are five strategies that aimed at assessing knowledge and attitudes, improving hearing health education, facilitating information access, and evaluating the applied actions.